Self-reflective Tool for Early Childhood Education Teachers as a Way to a Competent Teacher (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Model of the teacher as a reflective practitioner has come to the fore in recent years. The students are considered a key actor in their own professional development. The aim is to present a tool for students' reflection and self-reflection. The tool was created to individualize the training of future teachers. The tool was implemented within all pedagogical practices of students of early childhood education and verified through students' reflective reports (N=91) at the University of West Bohemia in Pilsen. The tool helps students think about their professional development, plan sub-steps and set specific goals they want to achieve in the development of their professional competences. Students also chose different goals for their development, which corresponded to their different initial knowledge and experience.